Writing and Producing an Original Play: Kind Thing; Nice Thing - Rivkin, Megan L. (Tufts Archival Research Center, 2020)
A reflection on the process of writing and producing an original play, "Kind Thing; Nice Thing." Advisor: Noe Montez.